2022
DOI: 10.33462/jotaf.1075550
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Effects of Some Additives Added to the Mixture of Diesel and Safflower Biodiesel on Exhaust Emissions

Abstract: In this study, linas, a newly developed variety of the safflower plant, were used for biodiesel production. Fuel properties and exhaust emission values of biodiesel fuel (B100) and alternative blended fuels containing different volumetric amounts of diesel (M100), biodiesel (B100) and n-butanol (BU) or n-pentanol (P) (diesel / biodiesel / n-butanol and diesel / biodiesel / n-pentanol) were evaluated in comparison with the reference fuel diesel (M100). In addition, in the study, the effects of 2-ethylhexyl nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Furthermore, they suggested that the increased density of biodiesel compared with diesel fuel amplifies the total fuel mass, consequently leading to slightly higher CO 2 emission values. Similarly, Şahin and Mengeş [48] reported that with an increase in the biodiesel ratio (10% and 20%), the average CO 2 emission values of the fuels across all speeds exhibited increments ranging between 0.2% and 5%.…”
Section: Engine Performance Valuesmentioning
confidence: 77%
“…Furthermore, they suggested that the increased density of biodiesel compared with diesel fuel amplifies the total fuel mass, consequently leading to slightly higher CO 2 emission values. Similarly, Şahin and Mengeş [48] reported that with an increase in the biodiesel ratio (10% and 20%), the average CO 2 emission values of the fuels across all speeds exhibited increments ranging between 0.2% and 5%.…”
Section: Engine Performance Valuesmentioning
confidence: 77%
“…These stages encompass the processing of raw materials, execution of reactions, and purification of the final product in biodiesel production (Eryilmaz et al, 2022;Şahin and Mengeş, 2022).…”
Section: Biodiesel Production Stagesmentioning
confidence: 99%